Comparison of the configuration and capabilities of ORM libraries for Android - Serwin, Tomasz (Journal of Computer Sciences Institute, 2018)
The article discusses configuration and capabilities of object-relational mapping libraries for the Android operating system. It also presents previous comparisons of ORMs for mobile systems. Configuration methods and supported mappings from java to database types are described.